2013
DOI: 10.1093/pcp/pct161
|View full text |Cite
|
Sign up to set email alerts
|

A Glycine Soja 14-3-3 Protein GsGF14o Participates in Stomatal and Root Hair Development and Drought Tolerance in Arabidopsis thaliana

Abstract: It is well established that 14-3-3 proteins are key regulators of multiple stress signal transduction cascades. However, the biological functions of soybean 14-3-3 proteins, especially in plant drought response, are not yet known. In this study, we characterized a Glycine soja 14-3-3 gene, GsGF14o, which is involved in plant development and drought response. GsGF14o expression was greatly induced by drought stress, as evidenced by the quantitative real-time PCR and β-glucuronidase (GUS) activity analysis. GsGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 86 publications
7
58
1
Order By: Relevance
“…It has been reported that drought stress can directly alter the abundance of 14-3-3 proteins [94,95,96]. In addition, overexpression or silencing of the 14-3-3 protein genes can modulate drought tolerance of transgenic plants (e.g., Gossypium hirsutum and Arabidopsis ) [97,98]. These results imply that 14-3-3 proteins may have diverse regulatory roles in leaves under drought stress, and the involvement of each 14-3-3 protein in drought-response needs to be further elucidated.…”
Section: Drought Sensing and Signalingmentioning
confidence: 99%
“…It has been reported that drought stress can directly alter the abundance of 14-3-3 proteins [94,95,96]. In addition, overexpression or silencing of the 14-3-3 protein genes can modulate drought tolerance of transgenic plants (e.g., Gossypium hirsutum and Arabidopsis ) [97,98]. These results imply that 14-3-3 proteins may have diverse regulatory roles in leaves under drought stress, and the involvement of each 14-3-3 protein in drought-response needs to be further elucidated.…”
Section: Drought Sensing and Signalingmentioning
confidence: 99%
“…1C, module 3). In agreement, overexpressors of GsGF14o (a Glycine soja 14-3-3 protein) induce shorter root hairs in Arabidopsis (Sun et al, 2014), but it was not elucidated whether this affects AHA activity. Other proteins also modify AHA protein activity by phosphorylation (e.g.…”
Section: Auxin Signaling Targets That Trigger Cell Expansionmentioning
confidence: 99%
“…However, since reversible phosphorylation of a protein alone is insufficient to complete the interaction directly, 14-3-3s, as crucial adaptor proteins are of great importance in plants because they bind phosphorylated peptides in the regulation of a diversity of processes (Denison et al, 2011), notably primary metabolism (Comparot et al, 2003; Diaz et al, 2011) and light (Sullivan et al, 2009; Taoka et al, 2011) and hormone signaling pathways (Ishida et al, 2004; Schoonheim et al, 2007; Gokirmak et al, 2010; Wang H. et al, 2011). In recent years, an increasing number of studies have shown that 14-3-3s also play important roles in how plants respond to a variety of biotic (Li et al, 2014; Teper et al, 2014) and abiotic (Chen et al, 2006; Sun et al, 2014; Zhou et al, 2014; He et al, 2015) stresses via the binding of the phosphorylated target proteins (Obsil and Obsilova, 2011). …”
Section: Introductionmentioning
confidence: 99%